Writing the half of it: a challenge unique to picture book authorship. Issue 1 (2nd January 2019) - Watkins, Ross
ABSTRACT: The picture book is a complex narrative form which makes use of not only literary devices but also visual devices, taking into account the content of the illustrations themselves as well as the way design principles lever and help deliver meaning for the reader. The story a picture book tells – as a form which goes beyond the script – is thereby dependent on more than one mode of discourse. For the writer – authoring what is essentially half the story at most – the nature of the form creates challenges which are unique to picture book authorship. I aim to contribute to the existing critical thinking on the picture book by: mapping the context of scholarly and practice-based discussion; outlining foundational concepts regarding the counterpointing use of visual and verbal modes; and introducing the use of anticipation, direction and accommodation as essential strategies which the picture book author must negotiate. I demonstrate these practices in relation to how other picture book authors have articulated their processes, as well as using my own experience as the author of One Photo (Watkins, Ross, and Liz Anelli. 2016. One Photo . Melbourne: Penguin Random House) as a case study.